Profile and Level of Competence of Information and Communications Technology (ICT) Coordinators among Secondary Schools in the Division of Davao del Sur - Araiz, Julcon (JPAIR Multidisciplinary Research, 2018)
ICT Coordinators play a significant role in the effective delivery of education in every school. There have been many studies carried out in relation to ICT, but less has been done dealing specifically with ICT Coordinators. The study aimed to find out the Level of Competence of ICT Coordinators in the 57 Secondary Schools in the Division of Davao del Sur, Philippines. A descriptive-correlational method was used in the study. The research instrument patterned to the NICS developed by the CICT (2006) was used in the data-gathering procedure. Data were analyzed using mean, chi-square, pearson r correlation coefficient and t- test. Results showed that ICT coordinators were intermediate in Technology Operations and Concepts, Social and Ethical, and Pedagogical Domains, but basic in the Professional domain. Likewise, significant relationships were not established with regard to their gender, age, educational attainment, length of service and position. The findings suggest that ICT Coordinators need to upgrade their level of competence in the Professional Domain to become more proficient and capable in performing their duties and responsibilities through seminar-workshops related to professional growth and development, research, innovation, and collaboration. To maintain their high level of competence, a continuing high-quality training program should be provided in the entire Secondary Schools in the Division of Davao del Sur.
Keywords: Information and Communication Technology; ICT Coordinators; descriptive-correlational method; Davao del Sur; Philippines